An Unusual Mechanism of Closure of Muscular Ventricular Septal Defects - Soham Dasgupta; Ashraf M. Aly (Hindawi Limited, 2017)
Ventricular septal defects (VSDs) are the most common congenital heart defects. Most of the small or moderate size (<6 mm) muscular VSDs close spontaneously within the first two years of life. The usual mechanism of spontaneous closure involves muscular tissue encroachment with superimposed fibrosis or primary fibrous tissue formation around the margins of the defect. We describe an unusual mechanism of spontaneous closure of a muscular VSD.